Gaya Bahasa Perbandingan dalam Kaba Urang Tanjung Karang pada Pertunjukan Dendang Pauah - Ananda, Refisa (Indonesian and Regional Language and Literature Department, Universitas Negeri Padang, 2024)
The purpose of this study is to describe the types and functions of comparative language styles in Urang Tanjuang Karang kaba in Dendang Pauah performances. The research method used in this study is a descriptive method with a form of qualitative research. The approach used in this study is a stylistic approach. The source of data in this study is kaba Urang Tanjuang Pauh in Dendang Pauh performance. The data analysis carried out was that researchers identified the comparative language style used in the Urang Tanjung Karang kaba. The results showed that the Urang Tanjuang Karang kaba contains a rich use of diction with the expression style of the old Minangkabau language. Parables are widely used to give a vivid picture of the characters and events in the kaba. The comparative language styles used are parables, hyperbole, litotes, metaphors, and personifications.